Peer victimization: theory, research, and practice - McGee, Zina T. (Bullying and victimization, 2021)
Background of the Problem within the Context of Youth Violence -- Urban Spaces and Environmental Systems among Youth Exposed to Violence -- Addressing Issues of Peer Victimization and Gun Violence among Youth -- Timeliness of Findings: Looking Ahead to the Problem of Youth Violence -- The Social Milieu of Youth Victimization.